Indonesia : Repeat Public Expenditure and Financial Accountability Report and Performance Indicators - World Bank (World Bank, Jakarta, 2015)
This public expenditure and financial accountability (PEFA) assessment for Indonesia was undertaken by a team of World Bank staff and development partners with close involvement of counterparts from the Government of Indonesia, including the ministry of finance, state ministry of development planning (Bappenas), and some line ministries. The objective of the assessment is to update the integrated, standardized, indicator-led assessment of public financial management (PFM) systems, processes, and institutions as a whole against good international practices. This PEFA assessment has been funded by the Bank and a multi-donor trust fund, supported by contributions from the European Commission, the Governments of the Netherlands and the Swiss Confederation, and United States Agency for International Development (USAID). This report focuses mainly on the changes in the performance of the PFM system from 2007 to 2011. This report focuses largely on the major changes since 2007, and also on the ongoing reforms that should impact an assessment in the future organizations. It provides an integrated, standardized, and indicator-led methodology to measure and monitor PFM performance over time. The objective is to help assess the performance of PFM systems, processes, and institutions relative to internationally recognized good system characteristics. The rating methodology, covering a set of 31 high level performance indicators, with over 70 dimensions, emphasizes empirical and observable facets for each PFM area.